The Transformation of Punggawa-Sawi Relationships and Fishing Technology in Baurung Village (1960–2024) - Lukman, Cici Nurmawaddah; Najamuddin, Najamuddin; Sakka, Abdul Rahma A (Papanda Publisher, 2025)
This study investigates the modernization of traditional fishermen in Baurung Village, Majene Regency, from 1960 to 2024, examining transformations in technology, economic structures, and socio-cultural dynamics. A qualitative historical approach was employed, incorporating heuristics, source criticism, interpretation, and historiography. Data were collected through semi-structured interviews with fishermen association leaders, active and senior fishermen, and fish distributors, complemented by participatory observation and documentary analysis. Triangulation and source criticism ensured data validity and reliability. The findings reveal that pre-modernization fishing relied entirely on traditional equipment such as baqgo and lepa-lepa, with social relations governed by kinship-based punggawa-sawi relationships. The introduction of katinting engines in the 1980s initiated technological transition, progressing to high-powered Mitsubishi 6D14 engines by the 2000s. This modernization increased monthly incomes to 10-15 million rupiah and expanded operational range beyond 50 kilometers offshore. However, modernization simultaneously produced economic stratification, transformed patron-client relationships into contractual arrangements, and paradoxically discouraged youth educational advancement due to attractive immediate maritime employment. Religious participation strengthened alongside improved prosperity. These findings demonstrate that modernization generates multidimensional impacts requiring integrated policy approaches that balance productivity enhancement with social equity and cultural preservation in coastal community development.